Perspektif Wisatawan Terhadap Brand Awareness Wisata Halal Sumatera Barat - Mifthah Ghufrani; Niken Febriana Ernungtyas (Jurnal Komunika Islamika : Jurnal Ilmu Komunikasi dan Kajian Islam, 2021)
Abstract: In the tourism industry, halal tourism is a different concept. Halal tourism is a tour that carries the concept of friendly Muslims for domestic and foreign Muslim tourists. Indonesia with a Muslim majority country has a lot of potential in the halal tourism industry sector. In the procurement of the halal tourism industry, this is implemented according to Islamic law. By providing a place of worship for Muslim tourists, prayer time info, lodging services that provide halal food and drinks, transportation services and other facilities. At present Indonesia has ten provinces with the title of the best halal tourist destination, one of which is the province of West Sumatra. However, the concept of halal tourism is still a lot of people and domestic tourists who do not know it yet. Awareness of halal tourism is also still unknown by the managers of attractions. This study aims to analyze tourist awareness about halal tourism in West Sumatra. In this study using descriptive qualitative methods, with 4 informants interview data collection techniques which are divided into 2 categories, namely, (1) tourists who have visited West Sumatra, and (2) tourists who have never been to West Sumatra. The results showed halal tourism in Indonesia is still classified as a new industrial sector. Travelers know the concept of halal tourism based on the management of tourist attractions that provide places of worship, halal food and beverage restaurants, and other supporting facilitation. And many tourists who are interested in visiting West Sumatra.